PENGARUH PERSEPSI RISIKO DAN DUKUNGAN PEMERINTAH TERHADAP MINAT PENGGUNAAN MOBILE BANKING: PERAN PEMEDIASI PERSEPSI KEGUNAAN - Maulidyati Aisyah; Tirta Ardami Ardiningsing (Universitas Ahmad Dahlan, 2022)
The Covid-19 pandemic has influenced the government to implement various policies as a form of support to break the chain of the spread of the Covid-19 virus. In addition, the presence of the Covid-19 pandemic requires people to switch from cash transactions to non-cash transactions to prevent exposure to the Covid-19 virus. Technological developments support this transition with the presence of mobile banking to facilitate non-cash transactions. This study aims to determine the effect of perceived risk and government support on interest in using mobile banking with perceived usefulness as a mediating variable. This type of research is quantitative research and uses a questionnaire to obtain data which is then processed using Structural Equation Modeling-Partial Least Square (SEM-PLS) software. The results of the study prove that risk perception has the most influence on interest in using mobile banking, while government support does not influence the use of mobile banking.